An AI-assisted positive matrix factorization framework for exploring sulfate, nitrate, and ammonium sources - Akshansha Chauhan; Yu-Cheng Chen; Chih-Da Wu; Nai-Tzu Chen; Chin-Yu Hsu; Ruei-Hao Shie (Environmental Pollution, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

Rational design of an oxime-functionalized probe for ultrasensitive and portable SERS detection of organophosphorus nerve agents - Qian Zhao; Hongwen Zhang; Jinglin Kong; Weiwei Liu; Da Chen; Zhenxing Cheng; Weiping Cai (Chemical Engineering Journal, 2026)

MXene and silver intercalated graphene oxide membrane with antibacterial performance for high-permeability micro/nanoplastics removal - Keqin Mi; Da Chang; Liangliang Zhang; Junli Lv; Yijia Liu; Mengmeng Cheng; Shifeng Hou (Journal of Environmental Chemical Engineering, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Hepatic cytochrome P450 induction following Kashin-Beck disease-related selenium deficiency and T-2 toxin exposure in mice - Tong Zhao; Yichen Zhao; Tingting Mao; Weixuan Da; Lina Qin; Li Liu; Huan Liu; Bolun Cheng; Yan Wen; Feng Zhang; Yumeng Jia (Archives of Toxicology, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

Sensitive fluorescent europium-organic framework sensor for selective discrimination of tetracycline and norfloxacin and applications in food samples - Chaodan Xiong; Liping Ren; Qiu-Hong Cheng; Xiang-Yu Zhang; Lijuan Liang; Kun Huang; Da-Bin Qin (Food Chemistry, 2026)

Enhancing source-level DC component of AC triboelectric nanogenerator via mirror asymmetry mechanism - Zhaojuan Shi; Sheng Zhang; Menghe Gao; Wenxuan Li; Yinxi Da; Zeming Guo; Jianjun Li; Qiang Tang; Cheng Xu (Chemical Engineering Journal, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Trichodermine A, a new polyketide from the endophytic Trichoderma sp. MH550506.1 associated with Gardenia jasminoides - Yan-Li Zhang; Jie-Zhen Shi; Tong-De Zhao; Han-Wei Ruan; Ju-Cheng Zhang; Jin-Hua Yu; Da-Mei Wang; Li-Feng Wang; Liang Deng; Dong Gan; Zhong-Tao Ding (Phytochemistry Letters, 2026)

Application of a sulfonic acid-modified NE probe with low-toxicity in a mouse model of pneumonia - Fei Gao; Kai Wang; Jin-Lu Song; Dong-Nv Wang; Da-Ke Wen; Feng-Ming Liang; You-Zhen Feng; Zhong-Yuan Cheng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Natural deep eutectic solvents assisted the encapsulation of curcumin in gellan gum hydrogels - Yu-Nan Pan; Jia-Cheng Liu; Lin-Da Zhang; Bin Lai; Ce Wang; Jia-Nan Yan; Hai-Tao Wu (Food Research International, 2026)

Artificial intelligence-enabled machine olfaction for volatile profiling and food quality decision-making - Yitian Gao; Jun-Hu Cheng; Han Wang; Yuandong Lin; Jinhua Wang; Da-Wen Sun (Food Chemistry, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Copolymer hydrogel formed by κ-carrageenan and chickpea protein amyloid fibrils: From rheological properties to regulation of aggregation morphology - Lin-Da Zhang; Xiao-Lei Zang; Yu-Nan Pan; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Hydrocolloids, 2026)

In-situ thiosulfate pretreatment enhances anaerobic fermentation of biodegradable plastic wastes into short-chain fatty acids: Degradation performance, microbial synergy and metabolic pathway - Boyi Cheng; Da Zhang; Qingshan Lin; Jinqi Jiang; Wugui Zou; Feixiang Zan; Shuai Zhou; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2026)

Coastal wetland classification using full-polarization SAR with polynomial feature generation and optimization algorithms - Zhenjin Li; Zhiyong Wang; Yuchu Fan; Da Liu; Zhaoxu Pang; Silong Cheng; Xiaomei Jiao (Advances in Space Research, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Effects of vertical stress and wetting path on undisturbed granite residual soil and slope failure mode transition - Yong-qing Chen; Zi-yu Liu; Shi-cheng Zhao; Peng Liu; Da-wei Huang; Xin Kang (Transportation Geotechnics, 2026)

Mechanistic insights into hexamethylphosphoramide degradation and phosphorus recovery via mZVI/O3: Beyond conventional oxidation through iron-phosphorus speciation - Da Wang; Wenqian Hu; Yumeng Zheng; Zihan Xia; Haijun Cheng; Xiaohui Lu; Zhiqiao He; Stefanos Giannakis; Shuang Song; Jun Ma (Chemical Engineering Journal, 2026)

Optimizing hydrogenation activation pathway in Cu-based hierarchical microspheres for sustainable nitrophenols hydrogenation with ultralow-reductant-consumption - Fengting Geng; Jiajia Cheng; Xuexin Niu; Xiaoli Wang; Hongxing Wang; Chaoyue Zhao; Ling Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Lifeng Cui; Longlong Geng (Chemical Engineering Journal, 2026)

Resampling native bee communities over 30 years showed stable trends along a tropical forest disturbance gradient - Qiaoyi Nong; Xiaojian Chen; Molin Hou; Da-Rong Yang; Michael C. Orr; Bai-Ge Miao; Cheng Wenda; Yan-Qiong Peng (Journal of Insect Conservation, 2026)

Portable smartphone-assisted fluorescence platform based on dual-excitation nitrogen-doped carbon dots for simultaneous detection of chlorogenic acid and tinidazole - Junyuan Shi; Zihang Yin; Dejin Lin; Dingfeng Wang; Siting Peng; Wendi Xiao; Houwen Hu; Jiong Cheng; Da Chen (Analytica Chimica Acta, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Upwelling-driven productivity and temperature-mediated diatom–dinoflagellate succession over the past 3000 years in the East China Sea - Zhangyu Cheng; Shuai Liu; Da-Wei Li; Wupeng Xiao; Yang Ding; Li Li; Meixun Zhao (Quaternary Science Reviews, 2026)

Self-catalyzed NiFe foam anode fabricated via tape-casting for oxygen evolution reaction in anion exchange membrane water electrolysis - Li-Da Chiu; Calvin Leo Putra; Shuo-En Yu; I-Chung Cheng; I-Chih Ni; Chih-I Wu; I-Chun Cheng; Jian-Zhang Chen (Fuel, 2026)

Self-triggered “Core-Shell” hydrogel sensor integrated with copper nano-aggregates for aquatic product freshness monitoring and preservation - Yajun Jin; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2026)

Geniposide ameliorates DSS-induced colitis via synergistically restoring intestinal barrier integrity and inhibiting the NF-κB-NLRP3-pyroptosis axis - Ximing Yang; Da Hong; Xiaoyu Ma; Yijiu Zhang; Li Liu; Shuzhen Cheng (Food Bioscience, 2026)

Lactoferrin-derived hydrophobic peptide YIYT alleviates osteoporosis via synergistic activation of Wnt/β-catenin and BMP/Smad pathways - Zhihui Chang; Da Hong; Xiaoyu Ma; Baifeng Fu; Shuzhen Cheng; Ming Du (Food Bioscience, 2026)

Microfluidic investigation on multiphase interaction behavior and carbon dissolution sequestration mechanisms during CO₂ injection in high-water-cut deep reservoirs - Xue Zhang; Qi’an Da; Chenxi Duan; Bin Huang; Cheng Fu; Dian Zhang; Lei Li; Yuliang Su (Chemical Engineering Journal, 2026)

Local ecological knowledge with stewardship sustains medicinal plants used by ethnic minorities in China - Da-Cheng Hao; Yan Wang; Dinghao Deng; Zhiduan Chen; Richard W. Spjut; Peigen Xiao (Trends in Ecology & Evolution, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Effects of hot air pretreatment on digestibility and quality of steamed bread - Yuze Jia; Jun-Hu Cheng; Xiangwei Tang; Xucong Yu; Da-Wen Sun (Food Chemistry, 2026)

Cold plasma-assisted enzymatic hydrolysis of shrimp protein for bioactive peptide production: Structural, antioxidant, and molecular docking characterization - Caidie Tang; Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2026)

Cyflumetofen induces hepatic steatosis and disrupts lipid metabolism in zebrafish larvae - Wei-Guo Wang; Yi-Min Duan; Da-Wei Yan; Lan Xu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang; Jia-Gao Cheng (Chemico-Biological Interactions, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Physiological and transcriptomic responses of a harmful algal bloom-causing dinoflagellate Karenia mikimotoi to multiple environmental factors - Can-Jun Cai; Wei-Ping Zhang; Zi-Cheng Dong; Ye-Hong Xin; Zhang-Xian Xie; Shu-Feng Zhang; Da-Zhi Wang (Water Research, 2026)

Dual-enhanced copper nanocluster sensing label via metal ion-induced aggregation for on-site seafood freshness monitoring - Yajun Jin; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Polycrystalline ferroelectricity in a molecular crystal for piezoelectric sensing - Gele Teri; Jing-Song Tang; Peng-Cheng Zhuge; Jia-Qi Luo; Hao-Fei Ni; Lei Pan; Qiang-Qiang Jia; Yi Zhang; Da-Wei Fu; Zhi-Xu Zhang (Chemical Engineering Journal, 2026)

Efficacy of copper alloy coatings in controlling Ichthyophthirius multifiliis infections: a sustainable alternative for freshwater aquaculture - Zi-Hong Guo; Wen-Hao Wu; Ming-Da Chen; Zi-Jian Long; Jian-Cheng He; Jia-Hao Zhang; You-Lu Su; Biao Jiang (Aquaculture, 2026)

Enhanced hydrolysis of cellobiose using vanadium-doped niobium phosphate: A water-tolerant solid acid catalyst with superior kinetic performance - Da-Ming Gao; Jianxing Zheng; Cheng-Bin Hong; Tong Wang; Xue-Chen Xu; Hidemi Fujino; Haichao Liu (Fuel, 2026)

Effects of cold plasma on volatile organic compounds in foods: fundamentals, mechanisms, and applications - Jun-Hu Cheng; Jin Li; Xiao Yang; Da-Wen Sun (Food Chemistry, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Synthesis, evaluation and preliminary clinical study of novel 68Ga-labeled Nectin-4 targeting PET tracer - Geng Hu; Zexin Xu; Da-Yong Hou; Pengcheng Ran; Liang Cheng; Wei Liu; Yue Zhao; Fan Jia; Xinyue Yang; Huihui You; Baoyuan Li; Hongxin Li; et al. (Chemical Engineering Journal, 2026)

A Conserved Bactericidal Permeability-Increasing Protein (BPI) Mediates Immune Sensing and Host Defense in the Hong Kong Oyster (Crassostrea hongkongensis) - Laiba Shafique; Yuwei Zhao; Muhammad Farhan Khan; Cheng Huang; Li Li; Peng Zhang; Peng Zhu; Da Zeng; Xueyu Yan; Bin Gong; Yongyan Liao; Youhou Xu; et al. (Fishes, 2026)
The bactericidal permeability-increasing protein (BPI) and lipopolysaccharide binding protein (LBP) are fundamental to innate immunity. However, their functional diversity and evolutionary conservation in ecologically crucial invertebrates, such as oysters, remain largely understudied. In this study, we identify and characterize a novel homolog of BPI/LBP, designated as ChBPI/LBP in the Hong Kong oyster (Crassostrea hongkongensis). Through structural and phylogenetic analysis, we identify ChBPI/LBP as a distinct member of the BPI protein family, with a high isoelectric point (pI of 9.26), indicating potent cationic BPI-like bactericidal function. We found that ChBPI/LBP is constitutively highly expressed at mucosal sites such as the gills and is rapidly upregulated in hemocytes following a challenge with Aeromonas hydrophila. Recombinant ChBPI/LBP demonstrated potent and specific bactericidal activity against Gram-negative pathogens. These findings suggest that ChBPI/LBP is an important antimicrobial peptide (AMP) effector in the oyster’s immune response. This work provides novel perspectives on the evolutionary mechanisms of innate immunity in bivalves and may have implications for disease management in aquaculture.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Accelerate transit network design problem-solving based on large-scale smart card data and graph-clustering decomposition - Da Lei; Long Cheng; Pengfei Wang; Xuewu Chen (Travel Behaviour and Society, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

CoFe@NiFe-LDH/CC bifunctional electrode: Mechanism and reactive oxygen species generation in the synergistic anodic oxidation and electro-Fenton processes - Bai-Chao Feng; Huai-Yuan Niu; Da-Wei Huang; Ming Yan; Cheng-Gang Niu (Journal of Cleaner Production, 2026)

Intestinal acinar adenocarcinoma in a blue-fronted Amazon parrot (Amazona aestiva) - João C. Krueger; Carolina Fontana; Arthur C. Cheng; Vinicius Dahm; Rachel Teixeira Neto; Luana Canavessi; Nelson D. Lucas; Luana C. Stunitz da Silva; Anderson Luiz de Carvalho; Aline de Marco Viott; Manoela M. Piva (Journal of Comparative Pathology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Inhibition of DRP1-mediated Mitochondrial Fission and NRF2/HO-1/GPX4-mediated Ferroptosis by Mdivi-1 Protects Against Vascular Cognitive Impairment - Xiao Ming Liu; Feng Chen; Yi Jun Cheng; Da Peng Wang (Molecular Neurobiology, 2026)

Microbial drivers of N₂O mitigation in soils: Role of nosZ II subclades under conservation tillage and stover mulching - Da-Cheng Hao; Yaoxuan Wang; Yuanyuan Luan; Fangbo Deng; Hongtu Xie; Yongxin Lin; Xuanqi Li; Zhongjun Jia; Lianfeng Wang (Applied Soil Ecology, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Cigarette butts: A hidden toxic time bomb for aquatic metabolism and behavior - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Environmental Pollution, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Effects of cold plasma-assisted alcalase on the structure, allergenicity and epitopes of shrimp tropomyosin - Caidie Tang; Jun-Hu Cheng; Hangyu Zhong; Jilin Li; Da-Wen Sun (Food Chemistry, 2025)

Spatiotemporal variations and risks assessment of PAH-bound suspended particles across different Asian countries: Insights from multi-city sampling and source apportionment - Kai Hsien Chi; Yen-Shun Hsu; Sheng-Lun Lin; Charles C.-K Chou; Somporn Chantara; Sereeter Lodoisamba; Thi Tuyet-Hanh Tran; Delgerzul Lodoisamba; Yuan Cheng Hsu; Chih-Da Wu; Tuan Hung Ngo; Shih Yu Pan (Environmental Research, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

OsSPT38 encodes a novel SUMO E3 ligase that improves rice stress resilience and grain yield - Zi-Sheng Zhang; Zheng-Yi Zhang; Jin-Qiu Xia; Si-Yan Chen; Liang-Qi Sun; Jie Wu; Da-Yu He; Jing-Xian Wang; Qin-Yu Liang; Lei Wang; Ke Ruan; Tian Sang; et al. (Molecular Plant, 2025)

Slow-released corrosive charge of zerovalent iron rendered superior Fenton-like catalysis: The tailored electron generation, transfer and utilization derived from spatial MoS2 encapsulation - Wei Da; Chi Zhang; Ai-Yong Zhang; Xianhui Yan; Cheng Chen; Lyumeng Ye (Journal of Hazardous Materials, 2025)

Metabolic saboteurs: Tire wear particles hijack energy economy of zooplankton - Hairong Lian; Chuhan Xu; Pengrui Xu; Da Tong; Zhizhong Li; Xinfeng Cheng; Kai Zhang; Xianling Xiang (Journal of Hazardous Materials, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Assessing 3-D variability of ultrafine particle using a Geo-AI modelling approach: A case study in Zhunan-Miaoli, Taiwan - Chia-Wei Hsu; Yinq-Rong Chern; Jun-Jun Su; Pei-Yi Wong; Aji Kusumaning Asri; Candera Wijaya; Yu-Cheng Chen; Shih-Chun Candice Lung; Ta-Chih Hsiao; Tee-Ann Teo; Yi-Liang Shih; Chih-Da Wu (Environmental Pollution, 2025)

Leveraging reinforcement learning for optimal control of chiller plant with complex hydraulic and thermodynamic characteristics - Xiao Wang; Huiming Xu; Cheng Fan; Shengyu Tan; Xuyuan Kang; Yang Shi; Da Yan (Energy and Buildings, 2025)

Ten questions concerning calibrating building energy simulation models - Adrian Chong; Da Yan; Kaiyu Sun; Sicheng Zhan; Siyu Cheng; Yi Wu; Yixing Chen; Tianzhen Hong (Building and Environment, 2025)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Structure-activity relationships and activity enhancement techniques of marine bioactive peptides (MBPs) - Cai-die Tang; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

Unveiling non-radical oxidation pathways in peroxymonosulfate/cobalt(II) systems: Critical role of cobalt(III) and cobalt(IV) explored by manganese(II) probing - Luwei Li; Xuecong Qian; Shilong Wang; Yun Liu; Da Wang; Huixin Zhang; Yechen An; Haijun Cheng; Jun Ma (Journal of Hazardous Materials, 2025)

Variation in dietary preference related the per- and polyfluoroalkyl substance exposure in two sympatric seabird species from the Yellow Sea, China - Yachang Cheng; Yuanyuan Liu; Yuanyuan Zhao; Da Zheng; Kaize Feng; Jinye Cheng; Jiansong Chu; Yang Liu; Jiachen Sun (Journal of Hazardous Materials, 2025)

Performance and feasibility assessment of near-isothermal compressed air energy storage in aquifers - Zifeng Cheng; Daniel Dias-da-Costa; Yixiang Gan; Sheng Jiang; Luming Shen (Journal of Cleaner Production, 2025)

Shaking table tests and numerical simulations of museum showcases subjected to floor motions - Pei Liu; Da-Cheng Hui; Hao-Tian Chen; Yuan-Ming Zhang (Engineering Structures, 2025)

Microplate - assisted local flow rate adjustment for regulation of droplet formation in coaxial microchannels - Jingjing Hou; Da Ruan; Yaqi Cheng; Xuehu Ma (Chemical Engineering Journal, 2025)

Comprehensive identification of crucial biomarkers and therapeutic targets in cholestasis via integrated single-cell RNA and transcriptome sequencing analysis - Cichun Wu; Da Cheng; Juan Mo; Nianqi Zhou; Shifang Peng; Lei Fu (Mammalian Genome, 2025)

Designing novel truncated aptamers for sensitive tropomyosin detection in shrimp products - Meixi Chen; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2025)

Fabrication of Ti-MOF/Ti3C2 heterojunction with boosted activity for visible light-driven photocatalytic degradation - Xianghan Cheng; Zhongmin Liu; Ruilin Wang; Yajun Guo; Wenyuan Han; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Suijun Liu; Longlong Geng (Journal of Environmental Chemical Engineering, 2025)

Elevating nanomaterial optical sensor arrays through the integration of advanced machine learning techniques for enhancing visual inspection of food quality and safety - Yuandong Lin; Jun-Hu Cheng; Ji Ma; Chenyue Zhou; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

A novel synergistic inhibition mechanism of pancreatic lipase by 2-mercaptobenzothiazole and stearic acid migrants from dairy contact rubbers - Yujie Wang; Juan Cheng; David Julian McClements; Jing Chen; Da Ma (Food Chemistry, 2025)

Current status and research progress of sugarcane stem borers management - Jin-Da Wang; Huan-Tai Lin; Xian-Kun Shang; Hong-Li Shan; Ji-Hu Li; Xue-Hong Pan; Jiong Yin; Cheng-Wu Zou; Bao-Shan Chen; San-Ji Gao (European Journal of Agronomy, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Acid-engineered UiO-66(Ce): From the limitations of concealed MOF sites to catalytic excellence for rapid atrazine degradation - Da Wang; Yufeng Ying; Liwen Cai; Haijun Cheng; Stefanos Giannakis; Gholamreza Moussavi; Zhiqiao He; Shuang Song; Jun Ma (Chemical Engineering Journal, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Evaluation of color photostability and structure of thylakoids in isolation and after undergoing food processing treatments - Xin-Yao Wen; Da-Cheng Feng; Pu Jing (Food Research International, 2025)

Nanoparticle contrast agent Mn3O4/SiO2/C as an ozonation catalyst with unexpected synergy in degrading organic contrast agent iopamidol: an effective “treat-waste-with-waste” strategy for medical wastewater - Wen Xu; Shiwen Dong; Haijun Cheng; Stefanos Giannakis; Xiaohui Lu; Zhiqiao He; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2025)

Nuclear translocation of β-catenin and migration of arecoline-induced oral cancer cells reduced by Taiwanin E via p-GSK3β downregulation - Chi-Cheng Li; Marthandam Asokan Shibu; Wei-Wen Kuo; Yueh-Hsiung Kuo; Yun-Peng Chao; Chun-Hsu Yao; Da-Tian Bau; Pei-Jei Lio; Chung-Jen Chiang; Chih-Yang Huang (Molecular & Cellular Toxicology, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Regulating bacterial biofilms in food and biomedicine: unraveling mechanisms and Innovating strategies - Jun-Hu Cheng; Rong Du; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2025)

Performance of cut-off walls under long-term vacuum suction: A case study - Chenchen Xu; Yongtao Hu; Shijie Han; Geng Xueyu; Da Cheng; Ning He; Yongfeng Deng (Marine Georesources & Geotechnology, 2025)

Impact of 2,4-di-tert-butylphenol on pancreatic lipase activity in emulsions: Multispectral, molecular docking, and in vitro digestion analysis - Weiyan Guan; Juan Cheng; David Julian McClements; Zongcai Tu; Jing Chen; Da Ma (Food Chemistry, 2025)

Object detection with attribute tagging task: Model design and evaluation on agricultural datasets - Da Liu; Pengguang He; Qingyu Wang; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Reduced graphene oxide prepared by cold plasma green treatment in liquid phase for fluorescence biosensing of tropomyosin in shrimp - Meixi Chen; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Unraveling phase-dependent variations of viral community, virus-host linkage, and functional potential during manure composting process - Zhengyuan Zhou; Songfeng Liu; Muhammad Saleem; Fei Liu; Ruiwen Hu; Hualong Su; Da Dong; Zhiwen Luo; Yongjie Wu; Yan Zhang; Zhili He; Cheng Wang (Bioresource Technology, 2025)

Revealed mechanism of 3D-open-microarray boosting exoelectrogens Geobacter enrichment and extracellular electron transfer for high power generation in microbial fuel cells - Da Liu; Chao-qun Xu; Wen-kai Fang; Cheng-yu Li (Bioresource Technology, 2025)

Carbon-dot pequi-nut in the development of immunosensor to detect pathogenic bacteria - Rachel Menezes Castelo; Marília de Albuquerque Oliveira; Roselayne Ferro Furtado; Bruno Peixoto de Oliveira; Lucas Vinicius Leite Martoni; Terezinha Feitosa Machado; Celli Rodrigues Muniz; Flávia Oliveira Monteiro da Silva Abreu; Sérgio Antônio Spinola Machado; Airis Maria Araújo Melo; Huai N. Cheng; Atanu Biswas; et al. (Brazilian Journal of Microbiology, 2025)

Metaproteomics reveals metabolic activities potentially involved in bloom formation and succession during a mixed dinoflagellate bloom of Prorocentrum obtusidens and Karenia mikimotoi - Hua-Min Cheng; Xiao-Lian Ning; Shu-Feng Zhang; Hao Zhang; Lin Lin; Si-Qi Liu; Da-Zhi Wang (Science of The Total Environment, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Enhancing moisture transfer and quality attributes of tomato slices through synergistic cold plasma and Osmodehydration pretreatments during infrared-assisted pulsed vacuum drying - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2025)

Temporal and spatial changes of glacial lakes in the central Himalayas and their response to climate change based on multi-source remote sensing data - Xiaoqiang Cheng; Donghui Shangguan; Chengsheng Yang; Wangping Li; Zhaoye Zhou; Xiaojie Liu; Da Li; Xiuxia Zhang; Huilan Ding; Zewei Liu; Yi Yu; Xiaoxian Wang; et al. (Global and Planetary Change, 2025)

Harnessing the polysaccharide production potential to optimize and expand the application of probiotics - Dong-Xu Ma; Hui-Juan Cheng; Hui Zhang; Shuo Wang; Xiao-Tao Shi; Xin Wang; Da-Chun Gong (Carbohydrate Polymers, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Catalytic oxidation of Mn(II) in the co-presence of Fe(II) by free chlorine: significance of in situ formed Mn(II)-doped Fe(III) oxides - Xuecong Qian; Shilong Wang; Haijun Cheng; Luwei Li; Yun Liu; Jinhao Duan; Da Wang; Jun Ma (Water Research, 2025)

Ferric ammonium citrate regulates iron death in mature porcine oocytes and their embryonic development in vitro through the NRF2 signaling pathway - Da Xu; Caifei Li; Yao Huang; Kaixin Hu; Cheng Wang; Pengyang Zhou; Haiying Shen; Chang Liu; Jiatong Xu; Jinyuan He; Jiaxu Jiang; Qi Qi; et al. (Theriogenology, 2025)

Fungal bioaugmentation enhanced herbicide removal via soil microbial fuel cell: Taking Myrothecium verrucaria and haloxyfop-P as an example - Da-Cheng Hao; Fan Wang; Chengxun Li; Yaoxuan Wang; Jiayi Xue; Pei-Gen Xiao (Science of The Total Environment, 2025)

Extraction of antimicrobial peptides from pea protein hydrolysates by sulfonic acid functionalized biochar - Min Liu; Xian-Da Hu; Xiang-Yu Huang; Li Wen; Zhou Xu; Li Ding; Yun-Hui Cheng; Mao-Long Chen (Food Chemistry, 2025)

Autonomous net inspection and cleaning in sea-based fish farms: A review - Jiaying Fu; Da Liu; Yingchao He; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Explore synergistic catalytic ozonation by dual active sites of oxygen vacancies and defects in MgO/biochar for atrazine degradation - Shiwen Dong; Luzhen Liu; Wen Xu; Haijun Cheng; Zhiqiao He; Feilong Dong; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Journal of Environmental Chemical Engineering, 2024)

Developing novel microwave-assisted induction heating (MAIH) technology for heating in-packaged ready-to-eat chicken breast products - Chiu-Chu Hwang; Yu-Ru Huang; Cheng-Da Hsieh; Yi-Chen Lee (Innovative Food Science & Emerging Technologies, 2024)

High sensitive Ratiometric fluorescent Aptasensor with AIE properties for Deoxynivalenol (DON) detection - Yuandong Lin; Nian Lu; Ji Ma; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Fabrication of Aspergillus oryzae lipase-immobilized magnetic Cu3(PO4)2∙3H2O nanoflowers for efficient synthesis of structured phospholipids - Hua-Wei Zhang; Ke Cheng; Jing-Jing Tang; Ling-Zhi Liu; Ruo-Xuan Qin; Yi-Nuo Sun; Jiang-Hua Zhang; Da-Yong Zhou (Food Bioscience, 2024)

Spatial and seasonal variations of atmospheric microplastics in high and low population density areas at the intersection of tropical and subtropical regions - Chien-Cheng Jung; Yuan-Chen Chao; Hui-Tsung Hsu; Da-Wei Gong (Environmental Research, 2024)

Efficient generation of Fe(IV) = O for water purification in periodate activation process: Reducing Fe orbital occupation and expanding electron transfer channel - Zheng-Tao Dong; Hai Guo; Ya-Ya Yang; Long Sui; Qian Wu; Xue-Gang Zhang; Cheng-Gang Niu; Ming Yan; Da-Wei Huang; Zhi-Liang Chen (Chemical Engineering Journal, 2024)

miR-144-3p Targets GABRB2 to Suppress Thyroid Cancer Progression In Vitro - Cheng Xiu; Xiaocong Deng; Da Deng; Tao Zhou; Chuiguang Jiang; Di Wu; Yong Qian (Cell Biochemistry and Biophysics, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

Rapid Adaption but Genetic Diversity Loss of a Globally Distributed Diatom in the Warmer Ocean - Luman Cheng; Xiuming Xu; Minghua Wang; Da‐Zhi Wang (Global Change Biology, 2024)
Studies have demonstrated that marine phytoplankton can adapt to the warmer environment. However, the underlying mechanisms remain largely unknown. Here, we quantified the capacity of a globally distributed marine diatom Skeletonema dohrnii , for rapid evolution under the moderate (24°C) and severe (28°C) warming scenarios. Whole‐genome resequencing analysis revealed that the evolutionary adaptation of S. dohrnii to moderate warming was slow (i.e., 700 generations), whereas it was rapid (i.e., 300 generations) under severe warming but suffered a substantial loss of genetic diversity within the population. Genes associated with energy production and lipid metabolism evolved rapidly, particularly under severe warming, suggesting their vital roles in thermal adaptation. Proteomic results also showed the enhanced expression of proteins involved in energy production and lipid metabolism, especially under severe warming. Furthermore, particulate organic carbon and nitrogen production was greatly enhanced in the moderate warming‐selected population but increased insignificantly in the severe warming‐selected population, indicating more rapid adaptation driven by severe warming. Our results provide molecular insights into the rapid but limited evolution of thermal adaptation in marine diatoms and highlight energy production and lipid metabolism as the most important adaptive strategy. Future warming will affect genetic diversity and population dynamics of diatoms in the ocean.

Monitoring interaction of shallowly buried, large-section, and long-distance twin box jacking tunnels with small spacing under the Beijing-Hangzhou Grand Canal - Zihao Chen; Pengpeng Ni; Cheng Cheng; Pengjiao Jia; Da Hu; Mengzhe Wu (Tunnelling and Underground Space Technology, 2024)

Recent selection and introgression facilitated high-altitude adaptation in cattle - Yang Lyu; Fuwen Wang; Haijian Cheng; Jing Han; Ruihua Dang; Xiaoting Xia; Hui Wang; Jincheng Zhong; Johannes A. Lenstra; Hucai Zhang; Jianlin Han; David E. MacHugh; et al. (Science Bulletin, 2024)

A fluorescent Aptasensor based on magnetic-separation strategy with gold nanoclusters for Deoxynivalenol (DON) detection - Nian Lu; Ji Ma; Yuandong Lin; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Leader RNA facilitates snakehead vesiculovirus (SHVV) replication by interacting with CSDE1 and hnRNP A3 - Da Huang; Rui Cheng; Xiaodan Liu; JiaQi Zhang; Chi Zhang (Fish & Shellfish Immunology, 2024)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

Real-time tilapia fillet defect segmentation on edge device for robotic trimming - Yingchao He; Weidong Xu; Da Liu; Maozhen Qu; Jiaying Fu; Fang Cheng (Computers and Electronics in Agriculture, 2024)

Efficient solution-processable OLEDs near BT.2020 red standard enabled by a multiresonant emitter - Hui Wang; Ying-Chun Cheng; Xiao-Chun Fan; Dong-Yang Chen; Xin Xiong; Xiao-Yao Hao; Yi-Zhong Shi; Jia Yu; Da Huang; Jia-Xiong Chen; Kai Wang; Xiao-Hong Zhang (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Novel cold plasma functionalized water pretreatment for improving drying performance and physicochemical properties of tomato (Solanum lycopersicum L.) fruits during infrared-accelerated pulsed vacuum drying - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Journal of Food Engineering, 2024)

Array-optimized artificial olfactory sensor enabling cost-effective and non-destructive detection of mycotoxin-contaminated maize - Maozhen Qu; Yingchao He; Weidong Xu; Da Liu; Changqing An; Shanming Liu; Guang Liu; Fang Cheng (Food Chemistry, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Mass transfer and mixing performance in jet-to-counterflow micromixer - Da Ruan; Yaqi Cheng; Jingjing Hou; Shidong Xue; Siyan Yang; Xuehu Ma (Chemical Engineering Journal, 2024)

Immune checkpoint-regulatable hydrogel-immobilized nanotherapeutics for post-surgical treatment of osteosarcoma - Da-Wang Zhao; Zhiliang Gao; Meng Si; Rui Hu; Xue Ma; Kaiwen Liu; Yixiang Zhao; Qiting He; Xiangzhen Kong; Chunwang Jia; Haoxin Zhai; Yuanqiang Zhang; et al. (Chemical Engineering Journal, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Innovative strategy for fabricating nanomaterials to ensure food safety by cold plasma: Principles, mechanisms, and applications - Jun-Hu Cheng; Lijuan Lan; Da-Wen Sun (Trends in Food Science & Technology, 2024)

Variation in leaf N allocation and mesophyll conductance to CO2 in four tree species under low soil P stress in subtropical China - Jingchao Tang; Baodi Sun; Ruimei Cheng; Zuomin Shi; Da Luo; Shirong Liu; Mauro Centritto (Acta Physiologiae Plantarum, 2024)

Refractory degradable dissolved organic matter (R-DOM) driving nitrogen removal by the electric field coupled iron‑carbon biofilter (E-ICBF): Performance and microbial mechanisms - Kai Cao; Xiao Huang; Cheng-Da Wang; Jiang-Hua Yu; Wen-Jing Gui; Shuai Zhang (Science of The Total Environment, 2024)

Unexpected weakened formation of disinfection byproducts and enhanced production of halates by cupric oxide during chlorination of peptide-bound aspartic acid - Guozhi Zhao; Mengjia Qiao; Haixiang Cheng; Da Xu; Xiaojuan Liu; Jun Hu; Zhimin Qiang; Dexin Wu; Qiaonv Chen (Journal of Hazardous Materials, 2024)

Fast real-time monitoring of meat freshness based on fluorescent sensing array and deep learning: From development to deployment - Yuandong Lin; Ji Ma; Da-Wen Sun; Jun-Hu Cheng; Chenyue Zhou (Food Chemistry, 2024)

Nonuniformity in stress transfer across FRP width of FRP-concrete interface - Peng-Da Li; Yao Zhao; Zhong Tao; Cheng Jiang (Engineering Structures, 2024)

Status and trends in the stability of the three largest ice shelves in Antarctica - Rongxing Li; Guojun Li; Lu An; Menglian Xia; Da Lv; Yuan Cheng; Aiguo Zhao; Tian Chang; Xiangbin Cui; Shengkai Zhang; Shijie Liu; Yixiang Tian; et al. (Science China Earth Sciences, 2024)

Assessment of co-benefits from on-road vehicle electrification in Suzhou City, China - Feiyue Qian; Cui Da; Chunchen Lu; Xinyu Gu; Junjian Yang; Chaowei Shi; Zhen Feng; Yuanyuan Cheng (Urban Climate, 2024)

The A subunit of vacuolar H+-ATPase gene (CmVHA-A) plays opposite roles in plant growth and drought tolerance of chrysanthemum under different growing conditions - Yan-Hong Liu; Zhen-Hao Zou; Man-Man Zhang; Zhang-Ji Guan; Lian-Da Du; Da-Gang Hu; Cheng-Shu Zheng; Cui-Hui Sun (Plant Science, 2024)

Assessing the influence of the COVID-19 pandemic on passengers' reliance on public transport - Long Cheng; Zhe Ning; Da Lei; Xinmei Cai; Xuewu Chen (Journal of Transport Geography, 2024)

Regulation of gene expression in the secondary metabolic synthesis pathway of Lonicera japonica Flos by yeast polysaccharides - Xu-peng Gu; Lin-lin Yang; Da-ming Qi; Di Zhang; Tian-liang Liu; Cheng-ming Dong (Physiology and Molecular Biology of Plants, 2024)

Establishing quality evaluation standards for pomelo fruit: The role of harvesting time and appearance characteristic - Xiaojun Yan; Muhammad Atif Muneer; Mengting Qin; Jie Ou; Xiaohui Chen; Zhiyuan He; Yedong Liu; Zhihan Cheng; Da Su; Rongrong Liu; Liangquan Wu (Postharvest Biology and Technology, 2024)

Soil water potential measurement using fiber-optic sensing technique - Jin-Jian Xu; Chao-Sheng Tang; Qing Cheng; Farshid Vahedifard; Da-Zhan Zhang; Chang Sun; Bin Shi (Journal of Hydrology, 2024)

New formula of vegetation roughness height and Darcy–Weisbach friction factor in channel flow - Da-Qian Feng; Jing-Jing Fan; Wei-Jie Wang; Cheng-Xing Xia; Ang Li (Journal of Hydrology, 2024)

Geospatial artificial intelligence for estimating daytime and nighttime nitrogen dioxide concentration variations in Taiwan: A spatial prediction model - Jennieveive Babaan; Pei-Yi Wong; Pau-Chung Chen; Hsiu-Ling Chen; Shih-Chun Candice Lung; Yu-Cheng Chen; Chih-Da Wu (Journal of Environmental Management, 2024)

Power improvement of triboelectric nanogenerator by morphological transformation strategy for harvesting irregular wave energy - Jianlong Wang; Zhenjie Wang; Da Zhao; Yang Yu; Xiaojun Cheng; Hengyu Li; Zhong Lin Wang; Tinghai Cheng (Chemical Engineering Journal, 2024)

Improved efficiency and stability using a novel elemental sulfur-based moving-bed denitrification process - Jia-Min Xu; Hu-Yi Zi; Hao-Ran Xu; Yi-Fan Zhang; Da-Heng Ren; Ran Zeng; Gui-Jiao Zhang; Aijie Wang; Hao-Yi Cheng (Water Research, 2024)

Unveiling microwave and Roasting-Steam heating mechanisms in regulating fat changes in pork using cell membrane simulation - Fengli Lian; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Chemistry, 2024)

Visible detection of chilled beef freshness using a paper-based colourimetric sensor array combining with deep learning algorithms - Yuandong Lin; Ji Ma; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Comparative elucidation of bioactive and antioxidant properties of red dragon fruit peel as affected by electromagnetic and conventional drying approaches - Edidiong Joseph Bassey; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2024)

Identification, distribution, bactericidal and immunoregulatory activities of NK-lysins in grass carp (Ctenopharyngodon idella) - Gai Ling Wang; En Zhong Li; Da Hong Li; Ming Cheng Wang; Shan Shan Sun; Run Yan Xiong; Chuan Feng Li; Bao Jian Sun; Hai Xia Xie (Aquaculture, 2024)

Identifying service bottlenecks in public bikesharing flow networks - Da Lei; Long Cheng; Pengfei Wang; Xuewu Chen; Lin Zhang (Journal of Transport Geography, 2024)

Ce-UiO-66-F4-based composites decorated with green carbon dots for universal adsorption of organic pollutants containing hydrogen bond donors and its application exploration - Maozhen Qu; Hengjie Yu; Yingchao He; Weidong Xu; Da Liu; Fang Cheng (Chemical Engineering Journal, 2024)

Thiosulfate/FeCl3 pre-treatment enhances short-chain fatty acid production and mitigates H2S generation during anaerobic fermentation of waste activated sludge: Performance, microbial community and ecological analyses - Boyi Cheng; Da Zhang; Qingshan Lin; Lichang Zhou; Jinqi Jiang; Xinqi Bi; Wei Jiang; Feixiang Zan; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2024)

Mapping hydrothermal alteration zones with short wavelength infrared (SWIR) spectra and magnetic susceptibility at the Pulang porphyry Cu-Au deposit, Yunnan, SW China - Cheng-Biao Leng; Da-Zhao Wang; Hai-Jun Yu; Feng Tian; Xing-Chun Zhang (Mineralium Deposita, 2024)

A machine learning-based ensemble model for estimating diurnal variations of nitrogen oxide concentrations in Taiwan - Aji Kusumaning Asri; Hsiao-Yun Lee; Yu-Ling Chen; Pei-Yi Wong; Chin-Yu Hsu; Pau-Chung Chen; Shih-Chun Candice Lung; Yu-Cheng Chen; Chih-Da Wu (Science of The Total Environment, 2024)

Inhibition of quorum sensing serves as an effective strategy to mitigate the risks of human bacterial pathogens in soil - Jinghan Zhang; Kun Lu; Lin Zhu; Na Li; Da Lin; Yangjuan Cheng; Meizhen Wang (Journal of Hazardous Materials, 2024)

Enhancing microorganism inactivation performance through optimization of plate-to-plate dielectric barrier discharge cold plasma reactors - Xiao Yang; Jun-Hu Cheng; Da-Wen Sun (Food Control, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Mitigating life-cycle environmental impacts and increasing net ecosystem economic benefits via optimized fertilization combined with lime in pomelo production in Southeast China - Xiaojun Yan; Yifei Ma; Kunpeng Kong; Muhammad Atif Muneer; Lijun Zhang; Yadong Zhang; Zhihan Cheng; Ziwei Luo; Changcheng Ma; Chaoyuan Zheng; Wenhao Yang; Jiuxin Guo; et al. (Science of The Total Environment, 2024)

Estimating morning and evening commute period O3 concentration in Taiwan using a fine spatial-temporal resolution ensemble mixed spatial model with Geo-AI technology - Chin-Yu Hsu; Ruei-Qin Lee; Pei-Yi Wong; Shih-Chun Candice Lung; Yu-Cheng Chen; Pau-Chung Chen; Gary Adamkiewicz; Chih-Da Wu (Journal of Environmental Management, 2024)

PARSIFAL: A toolkit for triple-GEM parametrized simulation - A. Amoroso; R. Baldini Ferroli; I. Balossino; M. Bertani; D. Bettoni; F. Bianchi; A. Bortone; A. Calcaterra; S. Cerioni; W. Cheng; G. Cibinetto; A. Cotta Ramusino; et al. (Computer Physics Communications, 2024)

Exposure estimates of PM2.5 using the land-use regression with machine learning and microenvironmental exposure models for elders: Validation and comparison - Chin-Yu Hsu; Wei-Ting Hsu; Ching-Yi Mou; Pei-Yi Wong; Chih-Da Wu; Yu-Cheng Chen (Atmospheric Environment, 2024)

Optimization of LSTM Parameters for Flash Flood Forecasting Using Genetic Algorithm - You-Da Jhong; Chang-Shian Chen; Bing-Chen Jhong; Cheng-Han Tsai; Song-Yue Yang (Water Resources Management, 2024)

Construction of methylation driver gene-related prognostic signature and development of a new prognostic stratification strategy in neuroblastoma - Yahui Han; Biyun Li; Jian Cheng; Diming Zhou; Xiafei Yuan; Wei Zhao; Da Zhang; Jiao Zhang (Genes & Genomics, 2024)

A unique subseafloor microbiosphere in the Mariana Trench driven by episodic sedimentation - Jiwen Liu; Da-Wei Li; Xinxin He; Ronghua Liu; Haojin Cheng; Chenglong Su; Mengna Chen; Yonghong Wang; Zhongsheng Zhao; Hanyue Xu; Zhangyu Cheng; Zicheng Wang; et al. (Marine Life Science & Technology, 2024)
Hadal trenches are characterized by enhanced and infrequent high-rate episodic sedimentation events that likely introduce not only labile organic carbon and key nutrients but also new microbes that significantly alter the subseafloor microbiosphere. Currently, the role of high-rate episodic sedimentation in controlling the composition of the hadal subseafloor microbiosphere is unknown. Here, analyses of carbon isotope composition in a ~ 750 cm long sediment core from the Challenger Deep revealed noncontinuous deposition, with anomalous 14 C ages likely caused by seismically driven mass transport and the funneling effect of trench geomorphology. Microbial community composition and diverse enzyme activities in the upper ~ 27 cm differed from those at lower depths, probably due to sudden sediment deposition and differences in redox condition and organic matter availability. At lower depths, microbial population numbers, and composition remained relatively constant, except at some discrete depths with altered enzyme activity and microbial phyla abundance, possibly due to additional sudden sedimentation events of different magnitude. Evidence is provided of a unique role for high-rate episodic sedimentation events in controlling the subsurface microbiosphere in Earth’s deepest ocean floor and highlight the need to perform thorough analysis over a large depth range to characterize hadal benthic populations. Such depositional processes are likely crucial in shaping deep-water geochemical environments and thereby the deep subseafloor biosphere.

A study on the mechanism of the impact of phenthoate exposure on Prorocentrum lima - Si-Wei Wu; Cai-Qin Cheng; Yi-Tong Huang; Jin-Zhou Tan; Song-Liang Li; Jia-Xin Yang; Xue-Ling Huang; Dan Huang; Li-Gong Zou; Wei-Dong Yang; Hong-Ye Li; Da-Wei Li (Journal of Hazardous Materials, 2024)

Predicting wheat gluten concentrations in potato starch using GPR and SVM models built by terahertz time-domain spectroscopy - Qingxia Li; Tong Lei; Yunlong Cheng; Xin Wei; Da-Wen Sun (Food Chemistry, 2024)

In vivo biological analysis of cold plasma on allergenicity reduction of tropomyosin in shrimp - Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2024)

Simultaneously tuning oxygen reduction pathway and charge transfer dynamics toward sacrificial agent-free photocatalytic H2O2 production for in-situ water disinfection - Ya-Ya Yang; Hai Guo; Da-Wei Huang; Lu Li; Hui-Yun Liu; Long Sui; Qian Wu; Jing-Jing Zhu; Lei Zhang; Cheng-Gang Niu (Chemical Engineering Journal, 2024)

Constructed electron-dense Mn sites in nitrogen-doped Mn3O4 for efficient catalytic ozonation of pyrazines: Degradation and odor elimination - Yinning He; Jiayi Li; Jingyu Tang; Haijun Cheng; Tao Zeng; Zhiqiao He; Da Wang; Lizhang Wang; Shuang Song; Jun Ma (Water Research, 2023)

Two new eudesmane sesquiterpenoids with neuroprotective activity from Pogostemon cablin - Qi Zheng; Chuan Ma; Liang Xiong; Cheng Peng; Li Guo; Da-Le Guo; E Zhao; Qin-Mei Zhou; Ou Dai (Phytochemistry Letters, 2023)

LF-NMR and MRI analyses of water status and distribution in pork patties during combined roasting with steam cooking - Fengli Lian; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Bioscience, 2023)

Mn(II) oxidation by the UV/chlorine system under near-neutral pH conditions: The important role of ClO· and ClO2 - Xuecong Qian; Shilong Wang; Haijun Cheng; Ziye Jia; Da Wang; Yandong Xie; Jinhao Duan; Yu Tian; Jun Ma (Water Research, 2023)

Effects of tillage patterns and stover mulching on N2O production, nitrogen cycling genes and microbial dynamics in black soil - Da-Cheng Hao; Xing-Yuan Su; Hong-Tu Xie; Xue-Lian Bao; Xu-Dong Zhang; Lian-Feng Wang (Journal of Environmental Management, 2023)

Synthesis of flower-shaped cyclodextrin microporous organic networks for selective recovery of acetophenone and 1-phenylethanol from petrochemical effluents - Yun-Da Yue; Yu Gao; Shi-Ya Fu; Yuan-Yuan Cui; Cheng-Xiong Yang (Chemical Engineering Journal, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Development of all-cellulose sustainable composites from directionally aligned bamboo fiber scaffold with high strength, toughness, and low thermal conductivity - Cheng Qian; Yu-Tian Wang; Chun Shi; Hao-Ying Wang; Hai-Yan Yang; Jing Yang; Da-Wei Wang; Zheng-Jun Shi (Chemical Engineering Journal, 2023)

Transcriptomics Meta-Analysis Reveals Phagosome and Innate Immune System Dysfunction as Potential Mechanisms in the Cortex of Alzheimer’s Disease Mouse Strains - Michael Anekson Widjaya; Chia-Hsin Liu; Shin-Da Lee; Wei-Chung Cheng (Journal of Molecular Neuroscience, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Loss of OsARF18 function confers glufosinate resistance in rice - Jin-Qiu Xia; Da-Yu He; Qin-Yu Liang; Zheng-Yi Zhang; Jie Wu; Zi-Sheng Zhang; Jing Zhang; Lin Wang; Cong-He Zhang; Ping-Xia Zhao; Cheng-Bin Xiang (Molecular Plant, 2023)

Characterization of the vertical evolution of urban nocturnal boundary layer by UAV measurements: Insights into relations to cloud radiative effect - Lin Shen; Jiaoshi Zhang; Yin Cheng; Xiaofeng Lu; Haosheng Dai; Dexia Wu; Da-Ren Chen; Jianguo Liu; Huaqiao Gui (Environmental Research, 2023)

Experiment study on reactive powder concrete beams using spirals reinforcement under torsion - Xia Cao; Yong-peng Quan; Yi-cheng Ren; Feng Fu; Qi-zhi Jin; Da-bo He; Yan Zheng (Engineering Structures, 2023)

Valorization of soybean plant wastes in preparation of N-doped biochar for catalytic ozonation of organic contaminants: Atrazine degradation performance and mechanistic considerations - Shiwen Dong; Xing Shen; Qingqing Guo; Haijun Cheng; Stefanos Giannakis; Zhiqiao He; Lizhang Wang; Da Wang; Shuang Song; Jun Ma (Chemical Engineering Journal, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

A pH-Responsive colourimetric sensor array based on machine learning for real-time monitoring of beef freshness - Yuandong Lin; Ji Ma; Da-Wen Sun; Jun-Hu Cheng; Qijun Wang (Food Control, 2023)

Phthalate exposure with sperm quality among healthy Chinese male adults: The role of sperm cellular function - Pan Yang; Lang-Jing Deng; Jin-Ying Xie; Xiao-Jie Li; Xiao-Na Wang; Bin Sun; Tian-Qing Meng; Cheng-Liang Xiong; Yi-Chao Huang; Yi-Xin Wang; An Pan; Da Chen; et al. (Environmental Pollution, 2023)

First report of leaf spot on Camellia sinensis caused by Neofusicoccum parvum in China - Xiaoyang Zhang; Xinen Yuan; Shuyuan Cheng; Da Huo; Haozhi Long; Bing Liu; Guihong Xiong; Junxi Jiang (Journal of Plant Pathology, 2023)

Mass balance of the Antarctic Ice Sheet from 2013 to 2018 estimated using the input-output method with updated remote sensing products - Yuan Cheng; Gang Hai; Xiangbin Cui; Da Lv; Gang Qiao; Rongxing Li (Science China Earth Sciences, 2023)

Thiosulfate pretreatment enhancing short-chain fatty acids production from anaerobic fermentation of waste activated sludge: Performance, metabolic activity and microbial community - Boyi Cheng; Yayi Wang; Da Zhang; Di Wu; Feixiang Zan; Jie Ma; Lei Miao; Zongping Wang; Guanghao Chen; Gang Guo (Water Research, 2023)

Unravelling the role of reactive oxygen species in ultrathin Z-scheme heterojunction with surface zinc vacancies for photocatalytic H2O2 generation and CTC degradation - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Chao Liang; Hai Guo; Ya-Ya Yang; Lu Li (Chemical Engineering Journal, 2023)

Functionalized graphitic carbon nitride based catalysts in solar-to-chemical conversion for hydrogen peroxide production - Chao Liang; Xue-Min Wang; Wei Liu; Hui-Yun Liu; Da-Wei Huang; Yuan-Zheng Zhang; Kai-Hang Zhang; Li-Sha Jiang; Yu-Yu Jia; Cheng-Gang Niu (Chemical Engineering Journal, 2023)

Lupus nephritis or not? A simple and clinically friendly machine learning pipeline to help diagnosis of lupus nephritis - Da-Cheng Wang; Wang-Dong Xu; Shen-Nan Wang; Xiang Wang; Wei Leng; Lu Fu; Xiao-Yan Liu; Zhen Qin; An-Fang Huang (Inflammation Research, 2023)

Study on the hydraulic parameter differences between pumping and recharge in a confined aquifer of a soft soil area - Gang Zheng; Qinghan Li; Xuesong Cheng; Xiaomin Liu; Jianwei Jia; Ying Jiao; Da Ha (Hydrogeology Journal, 2023)

Toxic reactive oxygen species stresses for reconfiguring central carbon metabolic fluxes in foodborne bacteria: Sources, mechanisms and pathways - Jun-Hu Cheng; Sang Zou; Ji Ma; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

Short-chain fatty acid production and phosphorous recovery from waste activated sludge via anaerobic fermentation: A comparison of in-situ and ex-situ thiosulfate-assisted Fe2+/persulfate pretreatment - Boyi Cheng; Da Zhang; Qingshan Lin; Shihao Xi; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Zongping Wang; Gang Guo (Science of The Total Environment, 2023)

Effects of dielectric barrier discharge cold plasma on structure, surface hydrophobicity and allergenic properties of shrimp tropomyosin - Jun-Hu Cheng; Jilin Li; Da-Wen Sun (Food Chemistry, 2023)

Novel sequential and simultaneous infrared-accelerated drying technologies for the food industry: Principles, applications and challenges - Obafemi Ibitayo Obajemihi; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2023)

A comprehensive review on nanocatalysts and nanobiocatalysts for biodiesel production in Indonesia, Malaysia, Brazil and USA - Hilman Ibnu Mahdi; Nurfadhila Nasya Ramlee; José Leandro da Silva Duarte; Yu-Shen Cheng; Rangabhashiyam Selvasembian; Faisal Amir; Leonardo Hadlich de Oliveira; Nur Izyan Wan Azelee; Lucas Meili; Gayathri Rangasamy (Chemosphere, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Effects of pretreatments using plasma functionalized water, osmodehydration and their combination on hot air drying efficiency and quality of tomato (Solanum lycopersicum L.) slices - Obafemi Ibitayo Obajemihi; Okon Johnson Esua; Jun-Hu Cheng; Da-Wen Sun (Food Chemistry, 2023)

A Geo-AI-based ensemble mixed spatial prediction model with fine spatial-temporal resolution for estimating daytime/nighttime/daily average ozone concentrations variations in Taiwan - Jennieveive Babaan; Fang-Tzu Hsu; Pei-Yi Wong; Pau-Chung Chen; Yue-Leon Guo; Shih-Chun Candice Lung; Yu-Cheng Chen; Chih-Da Wu (Journal of Hazardous Materials, 2023)

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Insights into the high performance of Co–Mn oxide supported by carbon fiber frameworks for ciprofloxacin oxidation process - Wen-Xin Fu; Meng-Zhu Qin; Huai-Yuan Niu; Qi-Yao Hu; Duan Guo; Ming-Ming Chen; Cheng-Gang Niu; Da-Wei Huang (Journal of Cleaner Production, 2023)

Enhancement of Wheat Seed Germination, Seedling Growth and Nutritional Properties of Wheat Plantlet Juice by Plasma Activated Water - Junhong Wang; Jun-Hu Cheng; Da-Wen Sun (Journal of Plant Growth Regulation, 2023)
Previous studies have shown the great potential of using plasma-activated water (PAW) on improving agriculture seed germination, however, information on the influence of PAW on crop plantlet juice remains scanty. In this research, the effect of PAW generated by atmosphere pressure Ar–O 2 plasma jet for 1–5 min on wheat seed germination, seedling growth and nutritional properties of wheat plantlet juice was investigated. Results revealed that all PAWs could enhance wheat seed germination and seedling growth in 7 days by improving the germination rate, germination index, fresh weight, dry weight and vigour index, and especially that PAW activated for 3 min (PAW-3) showed the best overall performance. In addition, the application of PAWs enhanced the nutritional properties of wheat plantlet juice from those grown for 14 days by improving total soluble solids, protein content, photosynthetic pigments, total phenolic content, antioxidant activity, enzyme activity, free amino acids and minerals content, and the best enhancement was also observed in PAW-3. It was concluded that PAWs would be an effective technique to enhance the growth and nutritional properties of crop sprouts, which could be served as functional foods in many forms.

Inhibitory effects of dielectric barrier discharge cold plasma on pathogenic enzymes and anthracnose for mango postharvest preservation - Yue Wu; Jun-Hu Cheng; Kevin M. Keener; Da-Wen Sun (Postharvest Biology and Technology, 2023)

Synergy between sulfur vacancy and Schottky junction into CoB/ZnIn2S4–S photocatalysts: Oriented charge flow and regulated carriers transfer dynamics to activate reactive oxygen species generation for efficient photocatalytic disinfection - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Meng-Ke Li; Ya-Ya Yang; Ning Tang; Lu Li; Lei Zhang (Journal of Cleaner Production, 2023)

Deconstruction of pineapple peel cellulose based on Fe2+ assisted cold plasma pretreatment for cellulose nanofibrils preparation - Hong Zhu; Jun-Hu Cheng; Ji Ma; Da-Wen Sun (Food Chemistry, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Single-kernel classification of deoxynivalenol and zearalenone contaminated maize based on visible light imaging under ultraviolet light excitation combined with polarized light imaging - Maozhen Qu; Shijie Tian; Hengjie Yu; Da Liu; Chao Zhang; Yingchao He; Fang Cheng (Food Control, 2023)

DNAzymes-conjugated upconversion nanoamplicon for in-situ ultrasensitive detection and imaging of microRNA in vivo - Yi Zhang; Da Luo; Yin Zhang; Qi-Hai Zhang; Qing-Yuan Ji; Shi-Kang Zhou; Shan Huang; Li-li Li; Feng Lu; Wei-Feng Yao; Fang-Fang Cheng; Jun-Jie Zhu; et al. (Chemical Engineering Journal, 2023)

Pyrite trace element and S-Pb isotopic evidence for contrasting sources of metals and ligands during superimposed hydrothermal events in the Dongping gold deposit, North China - Huan Li; Da-Peng Zhu; Thomas J. Algeo; Ming Li; Wei-Cheng Jiang; She-Fa Chen; Safiyanu Muhammad Elatikpo (Mineralium Deposita, 2023)

Cognitive changes are associated with increased blood-brain barrier leakage in non-brain metastases lung cancer patients - Da-Fu Zhang; Zhen-Hui Li; Zhi-Ping Zhang; Yin-Fu He; Bin-Li Shang; Xiu-Feng Xu; Ying-Ying Ding; Yu-Qi Cheng (Brain Imaging and Behavior, 2023)
To explore the relationship between cognitive function and blood–brain barrier leakage in non-brain metastasis lung cancer and healthy controls. 75 lung cancers without brain metastasis and 29 healthy controls matched with age, sex, and education were evaluated by cognitive assessment, and the Patlak pharmacokinetic model was used to calculate the average leakage in each brain region according to the automated anatomical labeling atlas. After that, the relationships between cognitive and blood–brain barrier leakage were evaluated. Compared with healthy controls, the leakage of bilateral temporal gyrus and whole brain gyrus were higher in patients with lung cancers ( P < 0.05), mainly in patients with advanced lung cancer ( P < 0.05), but not in patients with early lung cancer ( P > 0.05). The cognitive impairment of advanced lung cancers was mainly reflected in the damage of visuospatial/executive, and delayed recall. The left temporal gyrus with increased blood–brain barrier leakage showed negative correlations with delayed recall (r = -0.201, P = 0.042). An increase in blood–brain barrier leakage was found in non-brain metastases advanced lung cancers that corresponded to decreased delayed recall. With progression in lung cancer staging, blood–brain barrier shows higher leakage and may lead to brain metastases and lower cognitive development.

A cDNA-based reverse genetics system for feline calicivirus identifies the 3′ untranslated region as an essential element for viral replication - Jie Cheng; Aoxing Tang; Jing Chen; Da Zhang; Chunchun Meng; Chuanfeng Li; Hulai Wei; Guangqing Liu (Archives of Virology, 2023)

Ectopic expression of MmCYP1A1, a mouse cytochrome P450 gene, positively regulates stress tolerance in apple calli and Arabidopsis - Xiao-Na Wang; Fei Yang; Jiu-Cheng Zhang; Yi-Ran Ren; Jian-Ping An; Da-Yong Chang; Xiao-Fei Wang; Chun-Xiang You (Plant Cell Reports, 2023)

The pretreatment effects of various target pollutant in real coal gasification gray water by coupling pulse electrocoagulation with chemical precipitation methods - Bai-Hong An; Da-Mao Xu; Rui Geng; Yan Cheng; Rui-Bo Qian; Xian-Chun Tang; Zhi-Qiang Fan; Hong-Bin Chen (Chemosphere, 2023)

Using cluster algorithms with a machine learning technique and PMF models to quantify local-specific origins of PM2.5 and associated metals in Taiwan - Chin-Yu Hsu; Jhy-Charm Soo; Sheng-Lun Lin; Chih-Da Wu; Kai Hsien Chi; Wen-Chang Hsu; Chun-Chieh Tseng; Yu-Cheng Chen (Environmental Pollution, 2023)

Model development and validation of personal exposure to PM2.5 among urban elders - Wei-Ting Hsu; Chun-Hung Ku; Mu-Jean Chen; Chih-Da Wu; Shih-Chun Candice Lung; Yu-Cheng Chen (Environmental Pollution, 2023)

Study on artificial recharge and well loss in confined aquifers using theoretical and back-analysis calculations of hydrogeological parameters from recharge and pumping tests - Jianran Cao; Qinghan Li; Xuesong Cheng; Gang Zheng; Da Ha; Chaofeng Zeng (Bulletin of Engineering Geology and the Environment, 2022)

Xenoestrogen Status of Wuling Farm to Surrounding Water Bodies: An Application of Biochemical Parameters Using Onychostoma barbatulum - Lin-Yan Liao; Hui-Ling Cheng; Shu-Yin Wang; Shih-Hsiung Liang; Da-Ji Huang (Journal of Marine Science and Engineering, 2022)
The aim of this study was to apply biochemical parameters to Onychostoma barbatulum to understand whether Wuling Farm activities have caused organic pollution from xenoestrogens to flow into surrounding streams and thereby affected area aquatic ecosystems. Individuals of the Taiwan shovel-jaw carp (O. barbatulum) were collected by fyke netting in the Cijiawan, Kaoshan, and Yusheng Rivers in the protected area of Shei-Pa National Park and in the Ikawan River outside the protected areas from 4–5 June 2015 to 20–21 September 2015. The collected male individuals of O. barbatulum were divided into two groups. In the first group monooxygenase (Mon) activity, glutathione S-transferase (GST) activity, and vitellogenin (VTG) concentration in the liver were measured right after they were captured. Those in the second group were acclimated for 14 days and then exposed to 0 (control) or 10 ng/L 17β-estradiol for 10 days and then measured for changes in Mon, GST, and VTG in their livers. The value of VTG concentrations in O. barbatulum individuals collected from the Ikawan River was 2.12 ± 1.62 μg PO42+/g protein, which was the highest among all samples, followed by those collected from the Yusheng River (0.78 ± 1.00 μg PO42+/g protein). Individuals collected from the Yusheng River had the highest liver Mon activity (4.16 ± 1.08△A650/30 min/g protein) and the highest GST activity (1.58 ± 1.13 △A340/20 min/g protein), followed by those from the Ikawan River (Mon: 3.63 ± 1.13 △A650/30 min/g protein; GST: 1.24 ± 0.73 △A340/20 min/g protein). Comprehensive analyses showed that Mon and GST activities and VTG concentrations in livers measured right after being collected were lower than individuals exposed to 10 ng 17β-estradiol/L in the laboratory. Induced VTG concentrations were 9.87 ± 0.89 μg PO42+/g protein, Mon activity 8.02 ± 1.74 △A650/30 min/g protein, and GST activity 3.24 ± 0.62 △A340/20 min/g protein, indicating that farming activities have not significantly affected these aquatic organisms. However, pollution sources are still releasing pollutants containing xenoestrogens into the Yusheng River and Ikawan River. The impact of xenoestrogens is worthy of continuous long-term follow-up monitoring.

Genome-wide identification and expression analysis of JmjC domain–containing genes in grape under MTA treatment - Yi-Zhe Cheng; Guang-Qi He; Sheng-Di Yang; Shuai-Hui Ma; Jin-Ping Ma; Fang-Hui-Zi Shang; Xu-Fei Li; Hui-Ying Jin; Da-Long Guo (Functional & Integrative Genomics, 2022)

Greenhouse gas emission benefits of adopting new energy vehicles in Suzhou City, China: A case study - Cui Da; Xinyu Gu; Chunchen Lu; Ruiqi Hua; Xinyue Chang; Yuanyuan Cheng; Feiyue Qian; Yiheng Wang (Environmental Science and Pollution Research, 2022)

Association of caffeine and caffeine metabolites with obesity among children and adolescents: National Health and Nutrition Examination Survey (NHANES) 2009–2014 - Linling Yu; Hong Mei; Da Shi; Xing Wang; Man Cheng; Lieyang Fan; Yang Xiao; Ruyi Liang; Bin Wang; Meng Yang; Weihong Chen (Environmental Science and Pollution Research, 2022)

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Brain Reactions to Opening and Closing the Eyes: Salivary Cortisol and Functional Connectivity - Shen-Da Chang; Po-Chih Kuo; Karl Zilles; Tim Q. Duong; Simon B. Eickhoff; Andrew C. W. Huang; Arthur C. Tsai; Philip E. Cheng; Michelle Liou (Brain Topography, 2022)
This study empirically assessed the strength and duration of short-term effects induced by brain reactions to closing/opening the eyes on a few well-known resting-state networks. We also examined the association between these reactions and subjects’ cortisol levels. A total of 55 young adults underwent 8-min resting-state fMRI (rs-fMRI) scans under 4-min eyes-closed and 4-min eyes-open conditions. Saliva samples were collected from 25 of the 55 subjects before and after the fMRI sessions and assayed for cortisol levels. Our empirical results indicate that when the subjects were relaxed with their eyes closed, the effect of opening the eyes on conventional resting-state networks (e.g., default-mode, frontal-parietal, and saliency networks) lasted for roughly 60-s, during which we observed a short-term increase in activity in rs-fMRI time courses. Moreover, brain reactions to opening the eyes had a pronounced effect on time courses in the temporo-parietal lobes and limbic structures, both of which presented a prolonged decrease in activity. After controlling for demographic factors, we observed a significantly positive correlation between pre-scan cortisol levels and connectivity in the limbic structures under both conditions. Under the eyes-closed condition, the temporo-parietal lobes presented significant connectivity to limbic structures and a significantly positive correlation with pre-scan cortisol levels. Future research on rs-fMRI could consider the eyes-closed condition when probing resting-state connectivity and its neuroendocrine correlates, such as cortisol levels. It also appears that abrupt instructions to open the eyes while the subject is resting quietly with eyes closed could be used to probe brain reactivity to aversive stimuli in the ventral hippocampus and other limbic structures.

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Urinary polycyclic aromatic hydrocarbon metabolites and depression: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2016 - Xiaobing Feng; Ruyi Liang; Da Shi; Dongming Wang; Yanjun Guo; Weihong Qiu; Man Cheng; Tao Xu; Chaoqian Dong; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2022)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Insight into the α-glucosidase-inhibiting mechanism of β-PGG, a commonly occurring polyphenol in diets - Cheng-Di Huang; Hang-Hang Zheng; Xiao-Yue Zhang; Da-Zhi Liu; Jin-Ming Gao; Qiang Zhang (Natural Product Research, 2022)

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

Increased serum levels of cadmium are associated with an elevated risk of cardiovascular disease in adults - Siyu Ma; Jie Zhang; Cheng Xu; Min Da; Yang Xu; Yong Chen; Xuming Mo (Environmental Science and Pollution Research, 2022)

Distribution characteristics of per- and polyfluoroalkyl substances (PFASs) in human urines of acrylic fiber plant and chemical plant - Lin Peng; Wang Xu; Qinghuai Zeng; Yao Cheng; Yingjie Zhang; Ying Guo; Da Chen; Chao Jiang; Fei Wang (Environmental Science and Pollution Research, 2021)

Individual and combined influences of main loading parameters on granite damage development under ultrasonic vibration - Cheng Zhang; Da-jun Zhao; Shu-lei Zhang; Yu Zhou (Journal of Mountain Science, 2021)

Discriminating hydrocarbon generation potential of coaly source rocks and their contribution: a case study from the Upper Paleozoic of Bohai Bay Basin, China - Jinjun Xu; Da Lou; Qiang Jin; Lixin Fu; Fuqi Cheng; Shuhui Zhou; Xiuhong Wang; Chao Liang; Fulai Li (Frontiers of Earth Science, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Two new nor-sesquiterpenoids from Fusarium tricinctum , an endophytic fungus isolated from Ligusticum chuanxiong - Yu-Mei Cao; Da-Le Guo; Meng-Ying Jin; Lu Tan; Tian-Long Yang; Fang Deng; Yu-Cheng Gu; Xiao-Hua Li; Zhi-Xing Cao; Yun Deng (Natural Product Research, 2021)

Implantation of Bone Marrow Mesenchymal Stem Cells into Small Intestinal Submucosa Improves Bile Duct Injury in Rabbits - Ying Li; Piao Wang; Xiao-dong Hu; Jing-da Zeng; Cheng Fang; Yu Gan; Fang-yi Peng; Xiao-li Yang; De Luo; Bo Li; Song Su (Tissue Engineering and Regenerative Medicine, 2021)

On the driving factors of China’s provincial carbon emission from the view of periods and groups - Da Liu; Runkun Cheng; Xinran Li; Mengmeng Zhao (Environmental Science and Pollution Research, 2021)

The prograde-to-retrograde evolution of the Huangshaping skarn deposit (Nanling Range, South China) - Da-Peng Zhu; Huan Li; Thomas J. Algeo; Wei-Cheng Jiang; Chong Wang (Mineralium Deposita, 2021)

Inhibition of fruit softening by cold plasma treatments: affecting factors and applications - Ya-Wen Pan; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Multiple diversity facets of crucial microbial groups in biological soil crusts promote soil multifunctionality - Hua Li; Youxin Chen; Gongliang Yu; Federico Rossi; Da Huo; Roberto De Philippis; Xiaoli Cheng; Weibo Wang; Renhui Li (Global Ecology and Biogeography, 2021)
Aim Microbial diversity is one of the most important factors for maintaining the performance of multiple functions in soils (multifunctionality). However, existing studies typically consider the taxonomic richness or Shannon diversity of the entire community. We know little about the connection network of taxonomic and phylogenetic facets of diversity and their collective impact on multifunctionality. In this study, the linkages of effects of diversity within functional groups were disentangled in drylands. Location The central Tibetan Plateau. Time period Present. Major taxa studied Phototrophs and diazotrophs (mainly cyanobacteria). Methods Given the carbon‐ and nitrogen‐limited nature of drylands, we conducted a high‐throughput sequencing of C/N‐fixing functional groups from biocrusts and evaluated multiple facets of diversity (i.e., richness, evenness and phylogeny‐related trait dissimilarity), together with seven crucial variables of soil functioning to calculate multifunctionality. The relationships between multifaceted diversity and abundance with individual functions and multifunctionality were validated by a set of solid statistical analyses. Results We found that the integrated biodiversity index was a stronger predictor of multifunctionality than richness. The divergent performance of different facets of diversity determined the idiosyncratic effect of each functional group on soil multifunctionality. Moreover, the evaluation of functional significance at the species level gave important clues on the trade‐offs and redundancy in each functional group, explaining the distinct patterns of effects of diversity. Richness was the dominant factor for diazotrophs to maximize multifunctionality, whereas phylogenetic dissimilarity was the essential one for phototrophs. Main conclusions Our study demonstrated that multiple facets of diversity should be considered when assessing the effects of biodiversity. In contrast to the community level, within‐functional group measures might adequately capture the features of diversity that are most correlated with soil multifunctionality. Our results provide a perspective to bridge the gap between taxonomic and trait‐based approaches for elucidating the biodiversity–ecosystem function relationship.

Functionalization of water as a nonthermal approach for ensuring safety and quality of meat and seafood products - Okon Johnson Esua; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2021)

Aberrant methylation of the 16q23.1 tumor suppressor gene ADAMTS18 promotes tumorigenesis and progression of clear cell renal cell carcinoma - Ben Xu; Yi-ji Peng; Bing-lei Ma; Si-da Cheng (Genes & Genomics, 2021)

Populeuphrines A and B, two new cembrane diterpenoids from the resins of Populus euphratica - Kai-Xin Liu; Da-Peng Qin; Yan-Xia Zhu; Shao-Xiang Wang; Ya-Bin Jiao; Peng-Ling Ge; Yong-Xian Cheng (Natural Product Research, 2020)

Chemical, physical and physiological quality attributes of fruit and vegetables induced by cold plasma treatment: Mechanisms and application advances - Ya-Qi Chen; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2020)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

An effective biochar-based slow-release fertilizer for reducing nitrogen loss in paddy fields - Da Dong; Cheng Wang; Lukas Van Zwieten; Hailong Wang; Peikun Jiang; Minmin Zhou; Weixiang Wu (Journal of Soils and Sediments, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Salt tolerance and exclusion in the mangrove plant Avicennia marina in relation to root apoplastic barriers - Hao Cheng; Anifiok Inyang; Chang-Da Li; Jiao Fei; Yan-Wu Zhou; You-Shao Wang (Ecotoxicology, 2020)

Fungi isolated from host protocorms accelerate symbiotic seed germination in an endangered orchid species (Dendrobium chrysotoxum) from southern China - Shi-Cheng Shao; Qiu-Xia Wang; Kingly C. Beng; Da-Ke Zhao; Hans Jacquemyn (Mycorrhiza, 2020)

Stability evaluation of flat large-span cavern in jointed rock mass - Da-qing Kong; Chun-sheng Qiao; Gan-cheng Xue (Arabian Journal of Geosciences, 2020)

Three new ɑ-pyrone derivatives induced by chemical epigenetic manipulation of Penicillium herquei , an endophytic fungus isolated from Cordyceps sinensis - Da-Le Guo; Ling Qiu; Dan Feng; Xin He; Xiao-Hua Li; Zhi-Xing Cao; Yu-Cheng Gu; Ling Mei; Fang Deng; Yun Deng (Natural Product Research, 2020)

Multifunctionality of biocrusts is positively predicted by network topologies consistent with interspecies facilitation - Hua Li; Da Huo; Weibo Wang; Youxin Chen; Xiaoli Cheng; Gongliang Yu; Renhui Li (Molecular Ecology, 2020)
The potential of biodiversity loss to impair the delivery of ecosystem services has motived ecologists to better understand the relationship between biodiversity and ecosystem functioning. Although increasing evidence underlines the collective contribution of different biodiversity components on the simultaneous performance of multiple functions (multifunctionality), we know little about the trade‐offs between individual diversity effects and the extent to which they determine multifunctionality differentially. Here, at a subcontinental scale of 62 dryland sites, we show in phototrophic microbiota of biological soil crusts (biocrusts) that, whereas richness alone is unable to guarantee the maxima of multifunctional performance, interspecies facilitation and compositional identity are particularly stronger but often neglected predictors. The inconsistent effects of different biodiversity components imply that soil multifunctionality can be lost despite certain species remaining present. Moreover, we reveal a significant empirical association between species functional importance and its topological feature in co‐occurrence networks, indicating a functional signal of species interaction. Nevertheless, abundant species tend to isolate and merely interact within small topological structures, but rare species were tightly connected in complicated network modules. Our findings suggest that abundant and rare species of soil phototrophs exhibit distinct functional relevance. These results give a comprehensive view of how soil constructive species drive multifunctionality in biocrusts and ultimately promote a deeper understanding of the consequences of biodiversity loss in real‐world ecosystems.

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

CaMYC, A Novel Transcription Factor, Regulates Anthocyanin Biosynthesis in Color-leaved Pepper (Capsicum annuum L.) - Bo-Ya Lu; Guo-Xin Cheng; Zhen Zhang; Jian-Tian Sun; Muhammad Ali; Qing-Li Jia; De-Xu Luo; Zhen-Hui Gong; Da-Wei Li (Journal of Plant Growth Regulation, 2019)

3D density inversion of gravity gradiometry data with a multilevel hybrid parallel algorithm - Zhen-Long Hou; Da-Nian Huang; En-De Wang; Hao Cheng (Applied Geophysics, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Activities and conformation changes of food enzymes induced by cold plasma: A review - Yongxu Han; Jun-Hu Cheng; Da-Wen Sun (Critical Reviews in Food Science and Nutrition, 2019)

Callus of East Indian sandalwood co-cultured with fungus Colletotrichum gloeosporioides accumulates santalenes and bisabolene - Qingwei Cheng; Yuping Xiong; Meiyun Niu; Yueya Zhang; Haifeng Yan; Hanzhi Liang; Beiyi Guo; Xinhua Zhang; Jaime A. Teixeira da Silva; Youhua Xiong; Guohua Ma (Trees, 2019)

An ensemble-based likelihood ratio approach for family-based genomic risk prediction - Hui An; Chang-shuai Wei; Oliver Wang; Da-hui Wang; Liang-wen Xu; Qing Lu; Cheng-yin Ye (Journal of Zhejiang University-SCIENCE B, 2018)

Application of ensilage as a green approach for simultaneous preservation and pretreatment of macroalgae Ulva lactuca for fermentable sugar production - Zheng-Zher Wu; Da-Yuan Li; Yu-Shen Cheng (Clean Technologies and Environmental Policy, 2018)

Development and evaluation of a storm surge warning system in Taiwan - Mei-Ying Lin; Wen-Yih Sun; Ming-Da Chiou; Chih-Ying Chen; Hao-Yuan Cheng; Cheng-Hsin Chen (Ocean Dynamics, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Uhrf2 deletion impairs the formation of hippocampus-dependent memory by changing the structure of the dentate gyrus - Xiao-Rong Chen; Shi-Cheng Sun; Shuai-Wen Teng; Liang Li; Yi-Fan Bie; Hui Yu; Da-Li Li; Zhe-Yu Chen; Yue Wang (Brain Structure and Function, 2018)

Multiple strategies for increasing yields of essential oil and obtaining sandalwood terpenoids by biotechnological methods in sandalwood - Yueya Zhang; Haifeng Yan; Meiyun Niu; Qingwei Cheng; Xinhua Zhang; Jaime A. Teixeira da Silva; Guohua Ma (Trees, 2018)

Study of a full-wave equation-based seismic illumination analysis - Wei Liu; Cheng Yin; Dawei Li; Da Peng; Shulin Pan (Arabian Journal of Geosciences, 2017)

Quality analysis, classification, and authentication of liquid foods by near-infrared spectroscopy: A review of recent research developments - Lu Wang; Da-Wen Sun; Hongbin Pu; Jun-Hu Cheng (Critical Reviews in Food Science and Nutrition, 2017)

Identification of the Genetic Cause for Childhood Disintegrative Disorder by Whole-Exome Sequencing - Zhu Wen; Tian-Lin Cheng; Da-Zhi Yin; Shi-Bang Sun; Zheng Wang; Shun-Ying Yu; Yi Zhang; Zilong Qiu; Ya-Song Du (Neuroscience Bulletin, 2017)

Anti-apoptotic and Pro-survival Effects of Food Restriction on High-Fat Diet-Induced Obese Hearts - Yi-Yuan Lin; Po-Shiuan Hsieh; Yu-Jung Cheng; Shiu-Min Cheng; Chiao-nan Chen; Chih-Yang Huang; Chia-Hua Kuo; Chung-Lan Kao; Woei-Cherng Shyu; Shin-Da Lee (Cardiovascular Toxicology, 2017)

Emerging techniques for assisting and accelerating food freezing processes: A review of recent research progresses - Lina Cheng; Da-Wen Sun; Zhiwei Zhu; Zi Zhang (Critical Reviews in Food Science and Nutrition, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

An Estimation Method of Pore Structure and Mineral Moduli Based on Kuster-Toksöz (KT) Model and Biot’s Coefficient - Da Peng; Cheng Yin; Hu Zhao; Wei Liu (Acta Geophysica, 2016)

Lentiviral Vector-Mediated p27kip1 Expression Facilitates Recovery After Spinal Cord Injury - Min-hao Chen; Yong-hua Liu; Hua Xu; Da-wei Xu; Cheng-niu Wang; Yi- Wang; Cheng-wei Duan; Ying Zhou; Peng Kan; Ai-guo Shen; You-hua Wang (Molecular Neurobiology, 2016)

Elliptic Shape Prior Dynamic Programming for Accurate Vessel Segmentation in MRI Sequences with Automated Optimal Parameter Selection - Da-Chuan Cheng; Sin-Kuo Chai; Shi-Rong Xu; Shing-Hong Liu (Journal of Medical and Biological Engineering, 2016)

Plant regeneration via direct and callus-mediated organogenesis from leaf explants of Chirita swinglei (Merr.) W. T. Wang - Yulu Chen; Yueya Zhang; Qingwei Cheng; Meiyun Niu; Hanzhi Liang; Haifeng Yan; Xinhua Zhang; Jaime A. Teixeira da Silva; Guohua Ma (In Vitro Cellular & Developmental Biology - Plant, 2016)

Comparing Four Dimension Reduction Algorithms to Classify Algae Concentration Levels in Water Samples Using Hyperspectral Imaging - Hongbin Pu; Lu Wang; Da-Wen Sun; Jun-Hu Cheng (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

TDO as a therapeutic target in brain diseases - Cheng-Peng Yu; Ze-Zheng Pan; Da-Ya Luo (Metabolic Brain Disease, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Characteristics Analyses and Comparisons of the Protein Structure Networks Constructed by Different Methods - Shangli Cheng; Hua-Lin Fu; Da-Xiang Cui (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

A new partnership for an impactful future - Weimin Zhong; Da-Cheng Wang (Science China Life Sciences, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Calcitonin Gene-Related Peptide-Induced Calcium Alginate Gel Combined with Adipose-Derived Stem Cells Differentiating to Osteoblasts - Chang-zhi Huang; Xiao-ning Yang; Da-cheng Liu; Yi-gong Sun; Xing-ming Dai (Cell Biochemistry and Biophysics, 2015)
Calcitonin gene-related peptide (CGRP) has been confirmed with induction osteoblastic differentiation, but if it can make the three-dimensional culture of adipose-derived stem cells (ADSCs) to the osteoblastic differentiation, thus constructing tissue-engineered bone rare reports. To investigate the feasibility of exogenous CGRP-induced calcium alginate gel combined with ADSCs from rabbits in three-dimensional condition to construct tissue-engineered bone. ADSCs were obtained by collagenase I digestion of the subcutaneous adipose tissue of inguinal region of New Zealand rabbits. At the third passage, cells were mixed with sodium alginate to prepare calcium alginate gel, and the cells were assigned into two-group cultivates in 24 orifice plates. ADSCs in the control group were treated with DMEM/F-12 medium supplemented with 10 −2 mol/L β-glycerophosphate sodium, 10 −7 mol/L dexamethasone, 50 mg/L ascorbic acid, 0.1 % volume fraction of fetal bovine serum. ADSCs in the experimental group were incubated with the same medium as above, and in addition 1.5 µg/L CGRP was added. The cells proliferation and the mRNA expressions of collagen I and osteocalcin were detected by MTT and RT-PCR assays, respectively and alkaline phosphatase(ALP)and calcium concentration at different induction time were detected. The cell proliferation curves were S shaped. The OD values of experimental group were higher than those of control group at 1, 3, 5, 7, 14, and 21 days after osteogenic induction ( P < 0.05). ALP and alizarin red stains of ADSCs were all positive, but golden round nodes became bigger and more in the experimental group compared with the control group after 2 weeks. At 7 and 14 days, collagen I and osteocalcin mRNA expression were greater in the experimental group than the control group. ALP and calcium concentration of experimental group were higher than that of control group at 1, 2, 3, 4 weeks after osteogenic induction ( P < 0.05). Thus, these results show that the CGRP-induced ADSCs combined with calcium alginate gel to osteoblasts differentiation.

Applications of Near-infrared Spectroscopy in Food Safety Evaluation and Control: A Review of Recent Research Advances - Jia-Huan Qu; Dan Liu; Jun-Hu Cheng; Da-Wen Sun; Ji Ma; Hongbin Pu; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Experimental research on dynamic movement in strata overlying coal mines using similar material modeling - Kan Wu; Gong-Lin Cheng; Da-Wei Zhou (Arabian Journal of Geosciences, 2015)

Advances in Feature Selection Methods for Hyperspectral Image Processing in Food Industry Applications: A Review - Qiong Dai; Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng (Critical Reviews in Food Science and Nutrition, 2015)

A Potent Multi-functional Neuroprotective Derivative of Tetramethylpyrazine - Hai-Yun Chen; Da-Ping Xu; Guo-Lian Tan; Wei Cai; Gao-Xiao Zhang; Wei Cui; Jin-Zhao Wang; Cheng Long; Ye-Wei Sun; Pei Yu; Karl Wahkeung Tsim; Zai-Jun Zhang; et al. (Journal of Molecular Neuroscience, 2015)

Recent Advances in Methods and Techniques for Freshness Quality Determination and Evaluation of Fish and Fish Fillets: A Review - Jun-Hu Cheng; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Geochronological and geochemical constraints on the petrogenesis and geodynamic setting of the Qianlishan granitic pluton, Southeast China - Chun-Li Guo; Ru-Cheng Wang; Shun-Da Yuan; Sheng-Hua Wu; Bing Yin (Mineralogy and Petrology, 2015)

Mechanism of mining subsidence in coal mining area with thick alluvium soil in China - Da-Wei Zhou; Kan Wu; Gong-Lin Cheng; Liang Li (Arabian Journal of Geosciences, 2015)

Management of differentiated thyroid carcinoma with bone metastasis: a case report and review of the Chinese literature - Wei-dong Zhang; Da-ren Liu; Cheng-cheng Feng; Chuan-biao Zhou; Chen-ni Zhan; Ri-sheng Que; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

An efficient three-component synthesis of highly functionalized tetrahydroacenaphtho[1,2- $$b$$ b ]indolone derivatives catalyzed by L-proline - Juan-Juan Zhang; Xian Feng; Xue-Cheng Liu; Zhi-Bin Huang; Da-Qing Shi (Molecular Diversity, 2014)

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of heat softening on initiation of landslides - Chuan-xiang Xiong; Xiao-bing Lu; Wei-da Huang; Cheng-hua Wang (Journal of Mountain Science, 2014)

The prognostic value of osteopontin expression in non-small cell lung cancer: a meta-analysis - Tao Zhang; Dong-Ming Zhang; Da Zhao; Xiao-Ming Hou; Xiao-Jun Liu; Xiao-Ling Ling; Shou-Cheng Ma (Journal of Molecular Histology, 2014)

Serum microRNA-195 is down-regulated in breast cancer: a potential marker for the diagnosis of breast cancer - Fu-long Zhao; Yue-chao Dou; Xue-fei Wang; Da-cheng Han; Zhen-gang LV; Shuang-lei Ge; Ya-kui Zhang (Molecular Biology Reports, 2014)

The transcriptional response of apple alcohol acyltransferase (MdAAT2) to salicylic acid and ethylene is mediated through two apple MYB TFs in transgenic tobacco - Peng-Cheng Li; Shao-Wei Yu; Jin Shen; Qing-Qing Li; Da-Peng Li; De-Quan Li; Cheng-Chao Zheng; Huai-Rui Shu (Plant Molecular Biology, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Wave climate variability of Taiwan waters - Hwa Chien; Hao-Yuan Cheng; Ming-Da Chiou (Journal of Oceanography, 2014)

An improved method to extract DNA from mango Mangifera indica - Mohammad S. Uddin; Wenli Sun; Xinhua He; Jaime A. Teixeira da Silva; Qi Cheng (Biologia, 2014)

Effects of rainfall and manure application on phosphorus leaching in field lysimeters during fallow season - Qiao Yun Xue; Pei Bin Dai; Da Sheng Sun; Cheng Liang Sun; Ling Yu Qi; Anne Ostermann; Yao He; Xian Yong Lin (Journal of Soils and Sediments, 2013)

Responses of methane emissions and rice yield to applications of biochar and straw in a paddy field - Da Dong; Min Yang; Cheng Wang; Hailong Wang; Yi Li; Jiafa Luo; Weixiang Wu (Journal of Soils and Sediments, 2013)

Particle swarm optimization algorithm for analyzing SNP–SNP interaction of renin-angiotensin system genes against hypertension - Shyh-Jong Wu; Li-Yeh Chuang; Yu-Da Lin; Wen-Hsien Ho; Fu-Tien Chiang; Cheng-Hong Yang; Hsueh-Wei Chang (Molecular Biology Reports, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

The association between a single nucleotide polymorphism rs11966200 in MHC region and clinical features of generalized vitiligo in Chinese Han population - Jin Tang; Jian Lan Liu; Cheng Zhang; Da Yan Hu; Su Min He; Xian Bo Zuo; Pei Guang Wang; Liang Dan Sun; Xue Jun Zhang; Sen Yang (Molecular Biology Reports, 2013)

Oxidative decarboxylation of mandelic acid derivative by recombinant Escherichia coli: a novel method of ethyl vanillin synthesis - Xiao-xia Pan; Jing-jing Li; Mei-gui Wang; Wen-sen He; Cheng-sheng Jia; Xiao-ming Zhang; Biao Feng; Da-li Li; Zeng Zeng (Biotechnology Letters, 2013)

Comparative study on debris flow initiation in limestone and sandstone spoil - Ning-sheng Chen; Yang Lu; Ming-feng Deng; Da-wei Han; Hai-bo Zhou; Cheng-lin Yang (Journal of Mountain Science, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Expression of HOXD3 correlates with shorter survival in patients with invasive breast cancer - Cheng Shaoqiang; Zhang Yue; Liu Yang; Zhao Hong; Zhen Lina; Pang Da; Zhang Qingyuan (Clinical & Experimental Metastasis, 2013)

Alpha-momorcharin, a RIP produced by bitter melon, enhances defense response in tobacco plants against diverse plant viruses and shows antifungal activity in vitro - Feng Zhu; Ping Zhang; Yan-Fa Meng; Fei Xu; Da-Wei Zhang; Jian Cheng; Hong-Hui Lin; De-Hui Xi (Planta, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

The joint effect of cigarette smoking and polymorphisms on LRP5, LEPR, near MC4R and SH2B1 genes on metabolic syndrome susceptibility in Taiwan - Chuan-Wei Yang; Chia-Ing Li; Chiu-Shong Liu; Da-Tian Bau; Chih-Hsueh Lin; Wen-Yuan Lin; Tsai-Chung Li; Cheng-Chieh Lin (Molecular Biology Reports, 2013)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Seroprevalence of porcine cytomegalovirus and sapovirus infection in pigs in Hunan province, China - Guo-Hua Liu; Run-Cheng Li; Jing Li; Ze-Bin Huang; Chao-Ting Xiao; Wei Luo; Meng Ge; Da-Liang Jiang; Xing-Long Yu (Archives of Virology, 2012)

A glycine-rich RNA-binding protein can mediate physiological responses in transgenic plants under salt stress - Chao Wang; Da-Wei Zhang; Yu-Cheng Wang; Lei Zheng; Chuan-Ping Yang (Molecular Biology Reports, 2012)

Glypican-3, a novel prognostic marker of hepatocellular cancer, is related with postoperative metastasis and recurrence in hepatocellular cancer patients - Su Ning; Chen Bin; Huang Na; Shen Peng; Ding Yi; Ye Xiang-hua; Zeng Fang-yin; Zheng Da-yong; Luo Rong-cheng (Molecular Biology Reports, 2012)

Immunolocalization of chloride transporters to gill epithelia of euryhaline teleosts with opposite salinity-induced Na+/K+-ATPase responses - Cheng-Hao Tang; Lie-Yueh Hwang; I-Da Shen; Yu-Hui Chiu; Tsung-Han Lee (Fish Physiology and Biochemistry, 2011)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Adaptive evolution of context-dependent style curvature in some species of the Malvaceae: a molecular phylogenetic approach - Cheng-Jiang Ruan; Shi-Chao Chen; Qun Li; Jaime A. Teixeira da Silva (Plant Systematics and Evolution, 2011)

Induction of somatic embryogenesis from female flower buds of elite Schisandra chinensis - Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Optimization of Hydrolysis Conditions for the Production of the Angiotensin-I Converting Enzyme Inhibitory Peptides from Sea Cucumber Collagen Hydrolysates - Zun-Ying Liu; Da Chen; Yi-Cheng Su; Ming-Yong Zeng (Journal of Aquatic Food Product Technology, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Characteristics of CO2 release from forest soil in the mountains near Beijing - Xiang Yang Sun; Cheng Da Gao; Lin Zhang; Su Yan Li; Yong Qiao (Environmental Monitoring and Assessment, 2011)

Cerebellar Long-term Depression is Deficient in Niemann–Pick Type C Disease Mice - Cheng-Long Sun; Li-Da Su; Qiong Li; Xin-Xin Wang; Ying Shen (The Cerebellum, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Erratum to: Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

Exploitation of patchy soil water resources by the clonal vine Ficus tikoua in karst habitats of southwestern China - Chang-Cheng Liu; Yu-Guo Liu; Ke Guo; Da-Yong Fan; Li-Fei Yu; Rui Yang (Acta Physiologiae Plantarum, 2011)

In Vitro and In Vivo Anticancer Activity of a Novel Nano-sized Formulation Based on Self-assembling Polymers Against Pancreatic Cancer - Clare Hoskins; Mehdi Ouaissi; Sofia Costa Lima; Woei Ping Cheng; Inês Loureirio; Eric Mas; Dominique Lombardo; Anabela Cordeiro-da-Silva; Ali Ouaissi; Paul Kong Thoo Lin (Pharmaceutical Research, 2010)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

Application of SEBAL and Markov Models for Future Stream Flow Simulation Through Remote Sensing - Chih-Da Wu; Chi-Chuan Cheng; Hann-Chung Lo; Yeong-Keung Chen (Water Resources Management, 2010)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Style curvature and its adaptive significance in the Malvaceae - Cheng-Jiang Ruan; Jaime A. Teixeira da Silva; Pei Qin (Plant Systematics and Evolution, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Physicochemical evolution and positive selection of the gymnosperm matK proteins - Da Cheng Hao; Jun Mu; Shi Lin Chen; Pei Gen Xiao (Journal of Genetics, 2010)

Erratum to: Beginning a new Period celebrating the 60th anniversary of the journal Scientia Sinica—(Science China) - Da-Cheng Wang (Science China Life Sciences, 2010)

Trigonostemon tuberculatus (Euphorbiaceae), a peculiar new species from Yunnan Province, China - Du Fan; He Ju; Yang Shao-Yong; Cheng Xia; Zhang Da-Cai; Tang Ye-Na (Kew Bulletin, 2010)

Molecular evolution and positive Darwinian selection of the chloroplast maturase matK - Da Cheng Hao; Shi Lin Chen; Pei Gen Xiao (Journal of Plant Research, 2010)

Mesoscale barotropic instability of vortex Rossby waves in tropical cyclones - Wei Zhong; Han-Cheng Lu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2010)

A brief account on the study of the insulin crystal structure - Da-Cheng Wang; XiaoCheng Gu (Science China Life Sciences, 2010)

Beginning a new Period celebrating the 60th anniversary of the journal Scientia Sinica—(Science China) - Da-Cheng Wang (Science China Life Sciences, 2010)

Molecular phylogeny, long-term evolution, and functional divergence of flavin-containing monooxygenases - Da Cheng Hao; Shi Lin Chen; Jun Mu; Pei Gen Xiao (Genetica, 2009)

Branco River Stage Gradient Determination and Amazon Hydrologic Studies Using GPS Water Level Measurements - Kai-Chien Cheng; Stephane Calmant; Chung-Yen Kuo; Hong-Zeng Tseng; C. K. Shum; Frederique Seyler; Joecila Santos Da Silva (Marine Geodesy, 2009)

Modified biplanar open-wedge high tibial osteotomy with rigid locking plate to treat varus knee - Hai-ning Zhang; Jie Zhang; Cheng-yu Lv; Ping Leng; Ying-zhen Wang; Xiang-da Wang; Chang-yao Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Molecular evolution of paclitaxel biosynthetic genes TS and DBAT of Taxus species - Da Cheng Hao; Ling Yang; Beili Huang (Genetica, 2009)

Interspecific relationships and origins of Taxaceae and Cephalotaxaceae revealed by partitioned Bayesian analyses of chloroplast and nuclear DNA sequences - Da Cheng Hao; Pei Gen Xiao; BeiLi Huang; Guang Bo Ge; Ling Yang (Plant Systematics and Evolution, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Hypoxia-induced compensatory effect as related to Shh and HIF-1α in ischemia embryo rat heart - Jin-Ming Hwang; Yi-Jiun Weng; James A. Lin; Da-Tian Bau; Fu-Yang Ko; Fuu-Jen Tsai; Chang-Hai Tsai; Chieh-Hsi Wu; Pei-Cheng Lin; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2008)

Protective immunity of E. coli-synthesized NS1 protein of Japanese encephalitis virus - Cheng-Wen Lin; Kuang-Ting Liu; Hong-Da Huang; Wei-June Chen (Biotechnology Letters, 2008)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Genotypic and environmental variation in cadmium, chromium, arsenic, nickel, and lead concentrations in rice grains - Wang-da Cheng; Guo-ping Zhang; Hai-gen Yao; Wei Wu; Min Xu (Journal of Zhejiang University-SCIENCE B, 2006)

Inhibitory effect of medroxyprogesterone acetate on human liver cytochrome P450 enzymes - Jiang-Wei Zhang; Yong Liu; Wei Li; Da-Cheng Hao; Ling Yang (European Journal of Clinical Pharmacology, 2006)

Hg0 absorption in potassium persulfate solution - Qun-feng Ye; Cheng-yun Wang; Da-hui Wang; Guan Sun; Xin-hua Xu (Journal of Zhejiang University-SCIENCE B, 2006)

PCR-RFLP analysis ofcytochrome b gene does not supportCoilia ectenes taihuensis being a subspecies ofCoilia ectenes - Qi-Qun Cheng; Da-Ru Lu (Journal of Genetics, 2005)

Identification and genetic relationships of kenaf (Hibiscus cannabinus L.) germplasm revealed by AFLP analysis - Zhou Cheng; Bao-Rong Lu; Kazuhiko Sameshima; Da-Xu Fu; Jia-Kuan Chen (Genetic Resources and Crop Evolution, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)